(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Human Resources Management also deal with the facilities and requirements the Human Workforce are availing and need for their working process and carrier growth. It used to act as a bidirectional process flow which increase the â€œWorkforceâ€ and â€œSenior Managementâ€ and collaborate everybodyâ€™s requirements in a solution space and help to provide a better and value added service or outcome to customer or client of the organization. To make a human resource department more effective and efficient new technologies are now being introduced on a regular basis so make things much simpler and more modernized. One of the latest human resource technologies is the introduction of a Human Resources Information System. This integrated system is designed to help provide information used in HR decision making such as administration, payroll, recruiting, training, and performance analysis.